How can African agriculture adapt to climate change: Economywide impacts of climate change on agriculture in Sub-Saharan Africa - Calzadilla, Alvaro; Zhu, Tingju; Rehdanz, Katrin; Tol, Richard S.J.; Ringler, Claudia (International Food Policy Research Institute, 2009)
Approximately 80 percent of poor people in Sub-Saharan Africa continue to depend on the agricultural sector for their livelihoods, but-unlike in other regions of the world-agriculture in Sub-Saharan Africa is characterized by very low yields due to agroecological features, poor access to services, lack of knowledge and inputs, and low levels of investment in infrastructure and irrigation. In addition, high population growth rates, especially in rural areas, intensify pressure on agricultural production and natural resources and further complicate the challenge of reducing poverty. Against this background, potential climate change poses a significant additional challenge to the future of agriculture in the region. Climate change could cause serious deterioration of rural livelihoods and increase food insecurity in Sub-Saharan Africa. Given these multiple challenges, the region's smallholders and pastoralists must adapt, in particular by adopting technologies to increase productivity and the stability and resilience of their production systems.